Eclecticism Style in the Architecture of Khedivian Cairo - Enab, Mohamed (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2018)
Eclecticism style is one of the European architectural styles that have appeared in the buildings of Cairo in 13-14 A.H / 19-20A.D, which means the trend toward consolidation of various models and buildings in the previous civilizations and merge them and out in one building. This style has known as quoted-style or trend in architecture or eclectic architecture. The research is an attempt to Inventory these buildings that are built on this architectural style. This research follows the historical approach to knowing the origin of this architectural style and how it moved and spread in Cairo architecture in 1314 A.H / 1920 A.D. Then follows a descriptive and analytical approach of examples of these buildings built on this style, and analysis its architectural and artistic elements. In the end, the research has reached some critical results. For example, the primary purpose of this quotation and transportation is to give historical and technical value to these monuments. But unfortunately,Â the method of this quotation came in the wrong way. Thus losing the principle of unity and harmony that characterized the Islamic architecture, they unwittingly distorted the heritage value. These buildings became a collection of models that are not harmonious.